Transfer and commercialisation of contaminated groundwater remediation technologies. (28th August 2007) - Goltz, Mark N.; Williamson, Kenneth J.
High costs and poor performance of conventional groundwater remediation technologies have brought a call for the deployment of innovative technologies capable of attaining regulatory standards while satisfying time and budget constraints. To develop an innovative technology in the laboratory and ultimately transition it to full-scale commercialisation, presents challenges at various levels. Scientific and engineering problems and regulatory and legal issues exist that must be dealt with when moving a technology from the laboratory to the field. Importantly, cost and performance data must be presented in a manner that convinces stakeholders that the technology can accomplish remediation more economically, safely and efficiently than conventional technologies. The challenges of transferring and commercialising innovative groundwater remediation technologies and strategies that may be used to help overcome these challenges are discussed. Case studies of groundwater remediation technology transfer are presented.